To Live with Uncertainty - Curtiss, W. David (Tufts Archival Research Center, 2006)
W. David Curtiss describes how his well-laid life plans were interrupted by WWII, and how the uncertainty of war taught him to accept change, not with resignation, but with a spirit of adventure.